Synthesis and Biological Evaluation of Diversified Hamigeran B Analogs as Neuroinflammatory Inhibitors and Neurite Outgrowth Stimulators - Li, Ruo-Xin (Mar Drugs, 2020)
We describe the efficient synthesis of a series of new simplified hamigeran B and 1-hydroxy-9-epi-hamigeran B norditerpenoid analogs (23 new members in all), structurally related to cyathane diterpenoid scaffold, and their anti-neuroinflammatory and neurite outgrowth-stimulating (neurotrophic) activity. Compounds 9a, 9h, 9o, and 9q exhibited moderate nerve growth factor (NGF)-mediated neurite-outgrowth promoting effects in PC-12 cells at the concentration of 20 μm. Compounds 9b, 9c, 9o, 9q, and 9t showed significant nitric oxide (NO) production inhibition in lipopolysaccharide (LPS)-activated BV-2 microglial cells, of which 9c and 9q were the most potent inhibitors, with IC(50) values of 5.85 and 6.31 μm, respectively. Two derivatives 9q and 9o as bifunctional agents displayed good activities as NO production inhibitors and neurite outgrowth-inducers. Cytotoxicity experiments, H(2)O(2)-induced oxidative injury assay, and ELISA reaction speculated that compounds may inhibit the TNF-α pathway to achieve anti-inflammatory effects on nerve cells. Moreover, molecular docking studies provided a better understanding of the key structural features affecting the anti-neuroinflammatory activity and displayed significant binding interactions of some derivatives (like 9c, 9q) with the active site of iNOS protein. The structure-activity relationships (SARs) were also discussed. These results demonstrated that this structural class compounds offered an opportunity for the development of a new class of NO inhibitors and NGF-like promotors.